Achieved suitable dielectric swarm parameters for electrons in SF6 -Ne gas mixture. - Majeed, Raad Hameed (University of Thi-Qar Journal of Science, 2014)
There are two important types of basic gas-insulated apparatus used by electric power industry: i- gas-insulted transmission lines and ii- gas-insulated transformers. mixture are considered to be used in circuit breakers, neon has a very blow dielectric strength and contributes virtually nothing to the dielectric strength of the mixture. Neon however, complements in terms of its cooling capacity because it is very light, and does not react chemically either , or the gas impurities present in commercial , or the system components. The motion of electrons in plasma gas sulfur hexafluoride (SF6) and its mixture with inert gas in the present of applied uniform electric field is simulated by using the numerical solution of Boltzmann’s transport equation technique. The numerical solutions are utilized within the international computer code program called ’’NOMAD’’ written in FORTRAN 77, by using the Finite difference method. The energy distribution function and the swarm transport parameters of electron accelerated by DC electric field in a mixture of , are evaluated and compared with experimental result of drift velocity ( ), average energy ( ̅ ,characteristic energy ( ) , diffusion coefficient( ) ,and electron mobility ( ). We conclude that the calculation value has a Percentage agreement with international published experimental value over the range of E/N in Td units (E is the electric field and N concentration gas molecules). One can interpret the existence percentage error to the accuracy of the using cross section data for both elastic and inelastic collisions.